General overview of tomaticulture in the State in Goiás: a descriptive analysis from a bibliographic survey (Research, Society and Development, 2020)
This research aims to present an overview of tomato production in the state of Goiás, given the State's representativeness in the national production and commercialization of tomatoes. In this study, through analysis of secondary data available from official research agencies, the area destined to tomato cultivation, as well as the volume produced with a focus on the variety of table and a 10-year time frame. The results indicate, according to the official research institutions that the chains are analyzed in a common way, or prioritizing the segment for industrial purposes, with the information found according to the search criteria used, only at the Mauro Borges Institute of Statistics and Socioeconomic Studies - IMB , confirming the hypothesis that there is a lack of detailed and separate information on the two types of cultivation systems called creepers for industrial tomatoes and cuttings for table tomatoes, which can potentially restrict the sector’s competitiveness.